EFEITO DA COMPACTAÃ‡ÃƒO DE SOLO SOBRE O DESENVOLVIMENTO DA MAMONEIRA (ð˜™ð˜ªð˜¤ð˜ªð˜¯ð˜¶ð˜´ ð˜¤ð˜°ð˜®ð˜®ð˜¶ð˜¯ð˜ªð˜´ L.) - Savy Filho, Angelo; Castro, Orlando Melo de; Banzatto, Nicolau V. (REVISTA DE AGRICULTURA, 2020)
EFEITO DA COMPACTAÃ‡ÃƒO DE SOLO SOBRE O DESENVOLVIMENTO DA MAMONEIRA (ð˜™ð˜ªð˜¤ð˜ªð˜¯ð˜¶ð˜´ ð˜¤ð˜°ð˜®ð˜®ð˜¶ð˜¯ð˜ªð˜´ L.)